THE PRESENCE OF MICROPLASTICS IN MALE GONADS AND THEIR IMPACT ON FERTILITY (CIPEEX, 2025)
Introduction: Plastic, a synthetic polymer composed of carbon chains, facilitates modern life. Microplastics, with diameters between 0.1 and 5 mm, can be intentionally manufactured or generated from plastic degradation. They are environmental pollutants, present in food and water, and have been found in mammalian testes, including humans. Materials and Methods: This is an integrative review that used DeCS descriptors to search the Elsevier, MedLine, PubMed, and Cochrane databases, selecting articles according to the PICO strategy. Articles published between 2019 and 2024 in English and Portuguese were included. Initially, 39 articles were found, of which 6 were selected for review. Results: The interference of bisphenol A (BPA), di-n-butyl phthalate (DBP), polystyrene (PS), and polyvinyl chloride (PVC) in extracellular metabolism was demonstrated through lesions to Leydig cells. Three studies reported that nanoplastics induce testicular inflammation in mice, impairing gametes and testosterone production. Conclusion: Microplastics in testes may interfere with spermatogenesis and testosterone production.
Keywords: Men; Testosterone; Plastics